Real-world experience with upadacitinib induction for inflammatory bowel disease in Colombia: uparecol-induction - Parra-Izquierdo, Viviana (2025)
ntroduction: There are no studies on the efficacy and safety of upadacitinib for Inflammatory Bowel Disease (IBD) in Latin America. This study aims to describe its efficacy and safety during the induction phase in patients with moderate-to-severe IBD. Materials and methods: A multicenter observational descriptive study in IBD patients who received upadacitinib during the induction phase between July 2024 and January 2025. Results: A total of 26 patients were included, 53.8% female, with a mean age of 41.5 years (range 18.1-70.4; SD 17.5). Ulcerative colitis (UC) was present in 61.5% and Crohn’s disease (CD) in 38.5%, with a mean disease duration of 6.4 years. In UC, 62.5% achieved clinical response, 37.5% clinical remission, and 56.3% biochemical remission. In CD, 70% achieved clinical response, 20% clinical remission, and 50% biochemical remission. Nine of 16 UC patients (56.3%) and 3 of 10 CD patients (30%) achieved clinical remission of stool frequency and abdominal pain. In UC, there was a trend towards greater efficacy in urgency (OR 2.87; 95% CI: 0.53-18.25; p=0.19). Among 12 patients with extraintestinal manifestations (EIMs), 75% achieved remission. Adverse events were reported in 5 patients (19.3%): three cases of acne, one mild infection, and one severe infection. Conclusions: This first Latin American study on upadacitinib in IBD demonstrates its efficacy and safety in patients with moderate-to-severe disease activity.